The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/8796570
|View full text |Cite
|
Sign up to set email alerts
|

The Care Pathway Delays of Cervical Cancer Patient in Morocco

Abstract: Introduction. The aim of this study is to document time intervals in cervical cancer care pathways, from symptom onset to disease detection and start of treatment, and evaluate how clinical, sociodemographic, and treatment factors influence delays throughout a patient’s clinical pathway. Methods. A retrospective study was conducted at the FEZ Oncology Hospital of the Hassan II University Hospital Center in Morocco. Results. 190 medical records of cervical cancer patients were collected. The dominant age group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The longest patient delay was found by one assessment of 410 women in Ethiopia, with a median of 120 days ( 13 ). One exception is Morocco, where a research on 190 women found median patient and healthcare delays of 6 and 48 days, respectively ( 23 ). In the present study we observed the longest patient delay (median 304 days) thus far, and also the longest healthcare delay (median 61 days).…”
Section: Discussionmentioning
confidence: 99%
“…The longest patient delay was found by one assessment of 410 women in Ethiopia, with a median of 120 days ( 13 ). One exception is Morocco, where a research on 190 women found median patient and healthcare delays of 6 and 48 days, respectively ( 23 ). In the present study we observed the longest patient delay (median 304 days) thus far, and also the longest healthcare delay (median 61 days).…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 14 In the literature, patient delay is defined as an interval longer than 90 days between the discovery of the initial symptoms and diagnosis. 11 , 14 , 15 Studies conducted in Africa reported that the median patient delay in patients with cervical cancer ranged from 97 to 133 days 15 , 16 , 17 . One study that focused on women under 35 years of age showed that the median patient delay was 270 days (range, 90–720 days), which was significantly longer than that in the older group (270 vs. 60 days, P ​= ​0.0009).…”
Section: Introductionmentioning
confidence: 99%